Septic Pulmonary Embolism Causing Recurrent Pneumothorax in an Intravenous Drug User without Right-Sided Valvular Vegetation in Infective Endocarditis - Mason Montano; Kevin Lee; Kushal Patel; Mutsumi Kioka (Case Reports in Critical Care)
The following report illustrates a case of a 36-year-old Caucasian male with intravenous drug use (IVDU) induced septic thrombophlebitis presenting with recurrent unilateral pneumothoraces from septic pulmonary embolism (SPE) without the presence of obvious right-sided valvular vegetation in infective endocarditis (IE), defined as tricuspid or pulmonary valve lesions. Pneumothorax (PTX) has been observed as a rare complication of SPE and is commonly associated with infective right-sided IE, IVDU, and intravascular indwelling catheters. However, this case is novel as it is the very rare documented case of recurrent, unilateral, spontaneous right PTX refractory to multiple chest tube placements in such a setting. Therefore, the absence of detectable right-sided valvular vegetation in IE does not obviate the risk of SPE-induced PTX in IVDU and further expands the realm of infectious and pulmonary consequences of SPE and IVDU.